Conirmatory Factor Analysis of Depression, Anxiety and Stress 21 (DASS 21) scale in a study on Occupational Health Psychology in Health Care Professionals from Anand, Gujarat - Deepak B Sharma; Himanshu Sharma (Indian Association of Preventive and Social Medicine, 2023)
Introduction: Conirmatory factor analysis (CFA) is a statistical technique to verify the factor structure of a set of observed variables. Objective: The study was conducted with an objective to study the psychometric properties of DASS 21 scale by Conirmatory factor analysis. Method: This study used a Multi Method Design (Multiple approach Design), one was a cross sectional study of 228 participants and the other was a Solomon 4 group Design with total 64 participants. Four groups of health care professionals viz Allopathic doctors, Physiotherapists, Nursing professionals and Community Health Oficers (CHOs) were chosen for the study. Convenience sampling was done at two stages. Results: Conirmatory factor analysis was used to evaluate the construct validity of DASS 21 scale. The model was overidentiied as the estimated parameters were less than the number of observed variances and covariances. CMIN/DF (Chi square (minimum discrepancy function) /Degree of freedom) value was 2.021 which was < 5. Goodness of Fit Index (GFI) value (0.892) was near to .9. Root Mean square Residuals (RMR) and Root Mean Square Error of Approximation (RMSEA) value were 0.031 and 0.063, respectively which were less than 0.08. Average variance extracted (AVE) for the three constructs were less than the squared interconstruct correlation. Conclusion: DASS-21 scale demonstrated a good convergent validity, but in this study, discriminant validity was found to be poor as determined by average variance extracted in comparison to squared Interconstruct correlation.